2021
DOI: 10.1021/jacs.1c04288
|View full text |Cite
|
Sign up to set email alerts
|

Drum-like Metallacages with Size-Dependent Fluorescence: Exploring the Photophysics of Tetraphenylethylene under Locked Conformations

Abstract: Materials with aggregation-induced emission (AIE) properties are of growing interest due to their widespread applications. AIEgens, such as tetraphenylethylene units, display varying emission behaviors during their conformational changes. However, the structure–property relationships of the intermediate conformations have rarely been explored. Herein, we show that the conformational restriction on TPE units can affect the structural relaxation in the excited state and the resulting photophysical behaviors. Spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(41 citation statements)
references
References 43 publications
0
40
0
1
Order By: Relevance
“…This result indicated that the double‐decker SD with a rigid backbone might effectively suppress the energy loss via a non‐radiative transition process by restricting the intramolecular rotation or vibration of TPE moieties. [ 29 ] Interestingly, although the triple‐decker assemblies E‐ST, Z‐ST, and G‐ST comprise a higher number of TPE primitives, the phenyl groups of TPE without tpy substitution could slightly undergo rotation. Hence, these triple‐decker complexes showed a weaker emission than that of double‐decker SD.…”
Section: Resultsmentioning
confidence: 99%
“…This result indicated that the double‐decker SD with a rigid backbone might effectively suppress the energy loss via a non‐radiative transition process by restricting the intramolecular rotation or vibration of TPE moieties. [ 29 ] Interestingly, although the triple‐decker assemblies E‐ST, Z‐ST, and G‐ST comprise a higher number of TPE primitives, the phenyl groups of TPE without tpy substitution could slightly undergo rotation. Hence, these triple‐decker complexes showed a weaker emission than that of double‐decker SD.…”
Section: Resultsmentioning
confidence: 99%
“…Although most of the organic chromophores with nonplanar propeller geometry possess potential stimuliresponsiveness, [50] their luminescence responses in bulk states are weak or even imperceptible, mainly ascribed to the packing-induced rigidified molecular geometry and alignment. [25,51] In this work, given the coupled structural transformations of a 2D dynamic coordination space and the embedded chromophore, we then anticipated that this novel material may exhibit distinctive stimuli-responsive luminescent properties, with the hope of surpassing other types of smart luminescent materials.…”
Section: Resultsmentioning
confidence: 99%
“…COMMUNICATION aggregation-induced emission (AIE) properties ideally meet solid-state luminescent material requirements. [31][32][33][34][35] Herein, a supramolecular approach combining noncovalent copolymerization and fluorescence emission was used to construct underwater labeling materials. Bulk adhesives with strong adhesion capacity and luminescent behavior were designed and fabricated.…”
Section: Materials Horizonsmentioning
confidence: 99%